Sosialisasi dan Pelatihan Atur Pambiwara di Desa Dewutan Semanggi dalam Rangka Revitalisasi Budaya Jawa - Muhammad Sabandi; Alizta Marduama; Chamelia Martha Sasmita; Christina Wahyu Putri; Divani Sheva Zakiyatul Mufarridah; Febian Akbar Al Husaini; Helen Evy Kurniawati; Muhsin Ahmad Nursalim; Puspa Anggun Kharisma; Widya Astuti Wulandari (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
This community service activity aims to preserve Javanese culture, which is starting to be lost in today's society. Therefore, the UNS 66 FKIP KKN team held socialization and training on giving atur pambiwara. The presenter used several methods in this activity, such as a discussion method regarding the procedures for reading Javanese scripts properly and correctly, and the question-and-answer method to know the participants’ understanding and explore further material. Furthermore, simulation and practice methods were also used to give participants a real example and experience. The participants' engagement and participation were outstanding. The result of this programme was the emergence of a desire among residents to learn more about the Javanese language, particularly in giving atur pambiwara, as evidenced by the plans of residents who wanted to hold this activity regularly. This activity also gives an opportunity to cultivate residents' talents or interests, so hopefully, it can become a forum for channelling residents' interest in atur pambiwara activiti.